Home-based Hybrid Assistive Limb Lumbar Type Telerehabilitation in Spinocerebellar Ataxias : A Nonrandomized Open-label Trial - Kishimoto, Yoshiyuki; Yamada, Shinichiro; Hashizume, Atsushi; Ito, Daisuke; Komori, Shota; Kawase, Takahiro; Kondo, Ayano; Mori, Yu; Obara, Kazuki ; 0009-0006-5170-9169; Yamamoto, Munetaka; Kuwatsuka, Yachiyo; Ando, Masahiko; et al. (Cerebellum, 2025)
A hybrid assistive limb (HAL) can improve the motor performance of patients with various neurodegenerative diseases, but the efficacy of home-based rehabilitation using HAL for spinocerebellar ataxias (SCA) has yet to be elucidated. To evaluate the efficacy and safety of home-based telerehabilitation with lumbar type HAL in patients with SCA. In this non-randomized open-label single center trial, all participants underwent a 20-min home-based telerehabilitation program using the HAL lumbar type three times a week for 4 weeks. The primary outcome was the Timed Up and Go test (TUG), and secondary outcomes were the scale for the assessment and rating of ataxia (SARA), 10-m walk test, Berg Balance Scale (BBS), cerebellar cognitive affective/Schmahmann Syndrome Scale (CCAS-S), visual analogue scale, and clinical global impressions (CGI) scale. The assessments were conducted pre- and post-intervention and at 4 and 12 weeks after completion of the 4-week HAL rehabilitation. There was a non-significant mean change in TUG of − 1.3 s after the intervention (p = 0.051) but significant improvements in BBS (2.6 points; p = 0.011) and CCAS-S (3.7 points; p = 0.027). All participants completed the 4-week rehabilitation without any serious adverse events or dropout. Home-based telerehabilitation with HAL lumbar type is feasible and safe for patients with SCA. Despite its efficacy on TUG not being demonstrated, telerehabilitation improved balance and cognitive function in patients with SCA.
Publisher Copyright: © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.
Keywords: Cerebellar ataxia; Cognitive function; Exoskeleton device; Robotics; Telerehabilitation